Waqf management in the Perlis Islamic Religious Council : An analysis - Muhammad Syazuwan, Ahmad (2020)
Waqf properties contribute to a huge percentage of societal wealth in several Muslim countries. However, numerous Muslim countries are facing massive socio-economic problems such as poverty, education, and lack of basic healthcare services. This encourages contemporary Muslim scholars to formulate new financing methods that can be used to develop waqf properties and ensure that these modes confirmed with the Shariah. However, these methods are not maximumly been practiced in several states in Malaysia due to problems such as management, lack of funds, customer awareness, and others. Indeed, the applications of some of these financing methods have been proven successful in the development of Waqf properties. This paper attempts to critically review deeply on the main resources of waqf properties in Perlis, the current development of waqf properties as well as the issue in the management of waqf asset to aid the development of waqf properties in the Perlis Islamic Religious Council. By implementing qualitative research methods, this research design to ensure the finding of this study will give a massive contribution, especially to the Perlis Islamic Religious Council to practiced an instrumental approach to developing the waqf properties to meet urgent social needs of society. The study discusses the findings of the current waqf management practices in Perlis specifically on waqf development such as al-mudharabah, al-musharakah, almuzara’ah and implementation of cash waqf. Based on the findings, several recommendations are made on how best practices in waqf management can be adopted in the future.